Effectiveness of Using Canva-Based Learning Videos in Improving Critical Thinking Abilities of Elementary School Students: A Literature Study - Arini Dina Styowati; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
The background of this study is the importance of critical thinking skills in facing the challenges of the 21st century, where learning media plays a role as one of the factors that can support the development of these abilities, especially through learning videos. This study aims to determine the effect of using CANVA-based learning videos on students' critical thinking skills. This study uses a literature study method by collecting and analyzing data from various sources such as journals, books, and scientific articles that are relevant to the research topic. The results of the literature study show that the implementation of CANVA-based learning video media in elementary school learning can improve students' critical thinking skills. CANVA-based learning video media has proven effective in attracting students' attention, visualizing abstract concepts, and creating a pleasant learning atmosphere. The use of learning video media can also train students to analyze, evaluate, and draw conclusions from the information presented. It can be concluded that CANVA-based learning video media is an effective learning media to be implemented in improving elementary school students' critical thinking skills.